The β1-Adrenergic Receptor Contributes to Sepsis-Induced Immunosuppression Through Modulation of Regulatory T-Cell Inhibitory Function*. Issue 9 (18th February 2022) - Durand, Manon; Hagimont, Eugénie; Louis, Huguette; Asfar, Pierre; Frippiat, Jean-Pol; Singer, Mervyn; Gauchotte, Guillaume; Labat, Carlos; Lacolley, Patrick; Levy, Bruno; Glenn Chousterman, Benjamin; Kimmoun, Antoine
Abstract : OBJECTIVES: Although cardiovascular benefits of β1 -adrenergic receptor blockade have been described in sepsis, little is known about its impact on the adaptive immune response, specifically CD4 T cells. Herein, we study the effects of β1 -adrenergic receptor modulation on CD4 T-cell function in a murine model of sepsis. DESIGN: Experimental study. SETTING: University laboratory. SUBJECTS: C57BL/6 mice. INTERVENTIONS: High-grade sepsis was induced by cecal ligation and puncture in wild-type mice (β1 +/+ ) with or without esmolol (a selective β1 -adrenergic receptor blocker) or in β1 -adrenergic receptor knockout mice (β1 –/– ). At 18 hours after surgery, echocardiography was performed with blood and spleen collected to analyze lymphocyte function. MEASUREMENTS AND MAIN RESULTS: At 18 hours, β1 +/+ cecal ligation and puncture mice exhibited characteristics of high-grade sepsis and three surrogate markers of immunosuppression, namely decreased splenic CD4 T cells, reduced CD4 T-cell proliferation, and increased regulatory T lymphocyte cell proportions. Pharmacologic and genetic β1 -adrenergic receptor blockade reversed the impact of sepsis on CD4 T and regulatory T lymphocyte proportions and maintained CD4 T-cell proliferative capacity. β1 -adrenergic receptor blocked cecal ligation and puncture mice also exhibited a global decrease in both pro- and anti-inflammatory mediators and improved in vivo cardiovascular efficiency with maintained cardiac power index despite the expected decrease in heart rate. CONCLUSIONS: β1 -adrenergic receptor activation enhances regulatory T lymphocyte inhibitory function and thus contributes to sepsis-induced immunosuppression. This can be attenuated by β1 -adrenergic receptor blockade, suggesting a potential immunoregulatory role for this therapy in the management of sepsis.